Association between serum uric acid levels and achievement of target blood pressure among Japanese community residents with hypertension - Hirohide Yokokawa; Mai Suzuki; Nozomi Aoki; Hiroshi Fukuda; Yuki Sato; Teruhiko Hisaoka; Toshio Naito (The Journal of Clinical Hypertension, 2023)
Abstract The authors examined the sex‐specific association between serum uric acid (SUA) levels and achievement of target blood pressure among Japanese patients with hypertension. This cross‐sectional study was conducted between January 2012 and December 2015 and examined 17 113 eligible participants (6499 men; 10 614 women) with hypertension among 66 874 Japanese community residents who underwent voluntary health checkups. Multivariate analysis was used to estimate the association between high SUA level (≥7.0 mg/dL for men and ≥6.0 mg/dL for women) and “therapeutic failure” in achieving target blood pressure (BP) of 140/90 and 130/80 mmHg in both sexes. Multivariate analysis revealed that high SUA level was significantly associated with failure to achieve the 130/80 mmHg treatment goal among men (AOR = 1.24, 95% CI = 1.03–1.50, p = .03). Among women, high SUA level was significantly associated with failure to achieve both the 130/80 and 140/90 mmHg treatment goals (AOR = 1.33, 95% CI = 1.20–1.47, p < .01 and AOR = 1.17, 95% CI = 1.04–1.32, p < .01, respectively). Each increase in SUA quartile was positively associated with increases in systolic BP (SBP) and diastolic BP (DBP) (p < .01 for trend) in both sexes. SBP and DBP in each quartile (Q2–Q4) were also significantly higher compared with those of Q1 in both sexes (p < .01). Our data confirms the difficulties in maintain goal BP control in those with elevated SUA.